Integrating mobile Building Information Modelling and Augmented Reality systems: An experimental study - Chu, M.; Matthews, J.; Love, Peter (Elsevier BV, 2018)
© 2017 The benefits of Building Information Modelling (BIM) have typically been tied to its capability to support information structuring and exchange through the centralization of information. Its increasing adoption and the associated ease of data acquisition has created information intensive work environments, which can result in information overload and thus negatively impact workers task efficiency during construction. Augmented Reality (AR) has been proposed as a mechanism to enhance the process of information extraction from building information models to improve the efficiency and effectiveness of workers’ tasks. Yet, there is limited research that has evaluated the effectiveness and usability of AR in this domain. This research aims to address this gap and evaluate the effectiveness of BIM and AR system integration to enhance task efficiency through improving the information retrieval process during construction. To achieve this, a design science research approach was adopted that enabled the development and performance of a mobile BIM AR system (artefact) with cloud-based storage capabilities to be tested and evaluated using a portable desktop experiment. A total of 20 participants compared existing manual information retrieval methods (control group), with information retrieval through the artefact (non-control group). The results revealed that the participants using the artefact were approximately 50% faster in completing their experiment tasks, and committed less errors, when compared to the control group. This research demonstrates that a minor modification to existing information formats (2D plans) with the inclusion of Quick Response markers can significantly improve the information retrieval process and that BIM and AR integration has the potential to enhance task efficiency.